Using of perfectly matched layer (PML) in compucter simulation of the high-power relativistic plasma microwave amlifier - Bogdankevich, I.L.; Rukhadze, A.A.; Tarakanov, V.P. (Вопросы атомной науки и техники, 2005)
Computer simulation of the relativistic plasma microwave amplifier was made by using code KARAT. A pure amplification regime (without accompanying generation) was achieved in such amplifier in the experiment [1]. The simulation system was made nearly the same experimental setup. The main feature of this model is a microwave absorber. За допомогою коду КАРАТ [4,5] нам удалося чисельно промоделювати підсилювач, використовуючи поглинач у виді модельного середовища з заданими параметрами. Шляхом зміни параметрів поглинаючого середовища і коефіцієнта відображення вихідного дзеркала [3], удалося підібрати оптимальний режим посилення мікрохвильового випромінювання на заданій частоті. У широкому діапазоні зміни зазначених параметрів досягнуте посилення в 30 дБ. С помощью кода КАРАТ [4,5] нам удалось численно промоделировать усилитель, используя поглотитель в виде модельной среды с заданными параметрами. Путем изменения параметров поглощающей среды и коэффициента отражения выходного зеркала [3], удалось подобрать оптимальный режим усиления микроволнового излучения на заданной частоте. В широком диапазоне изменения указанных параметров достигнуто усиление в 30 дБ.